Аналіз надійності ПЛІС. Порівняння ризиків, пов’язаних з використанням ПЛІС і мікропроцесорів - Чумак, В. С.; Свид, І. В. (ХНУРЕ, 2020)
In the process of developing fault-tolerant and guaranteed systems, which begins with thorough preparation for the project and ends with multi-level verification and testing, the moment of choosing the optimal element base, which should meet certain requirements.
Keywords: ПЛІС; мікропроцесор; порівняння ризиків; порівняльний аналіз